The Youth as the Clients of Career Guidance: Selected Studies of Polish Adolescents - Piorunek, Magdalena (Wydawnictwo: Adam Marszałek, 2006)
This study attempts to find an answer to a question of how adolescents handle their educational and vocational career planning process in the context of cultural and economic transformations. It be-comes particularly important to know how to knowingly shape one's own vocational biography in the market environment characterized by competitiveness and high unemployment rate. A diagnostic questionnaire method was applied in the research. A statistical analysis of the research results demonstrated three groups of young people that handle their career planning in diverse ways: one applying perspective strategies, one preferring strategies that focus on the present only and one group including persons who gave up their planning of the future either following a conscious choice or due to practical helplessness. Each group requires different forms of counselling and educational support in shaping their vocation-al biographies and has different requirements towards vocational counselling. The counselling activi-ties, as demonstrated by the research results, require increasingly more psycho- and educational skills, significantly exceeding a narrowly defined professional orientation.
Keywords: planning of educational and vocational future; adolescence; vocational development of individuals; vocational counselling